Redescription of Bathymodiolus septemdierum Hashimoto and Okutani, 1994 (Bivalvia, Mytilida, Mytilidae), a mussel broadly distributed across hydrothermal vent locations in the western Pacific and Indian Oceans - Tunnicliffe, Verena; Breusing, Corinna (Zootaxa, 2022)
Mussels of the genus Bathymodiolus Kenk & Wilson belong to the foundation fauna at hydrothermal vents in the global deep sea. In the western Pacific and Indian oceans, the three nominal taxa B. septemdierum Hashimoto and Okutani, B. brevior Cosel, Métivier & Okutani and B. marisindicus Hashimoto are currently recognized as separate species despite morphological and genetic evidence for their conspecificity. All three are listed with the International Union for Conservation of Nature Red List based on highly restricted ranges. We compile and supplement existing morphometric and molecular data to revise the Bathymodiolus septemdierum species group. We redescribe B. septemdierum as a single species with B. brevior and B. marisindicus recognized as junior synonyms. Given the exceptionally broad range of B. septemdierum, we propose removal of these three taxa from the IUCN Red List.